European identity as a prerequisite for the efficient strategic management in the European Union: Tożsamość europejska jako warunek skutecznego zarządzania strategicznego w Unii Europejskiej - Basaj, Martyna; Kożuch, Bartosz (Management and Administration Journal, 2021)
The aim of the article is to demonstrate that the internal weakness of the European Union as an organization, which prevents effective strategic management, results from the lack of a single organizational identity. The national governments hinder the development of the Community Method, treating their interests as paramount. Therefore they counteract the EU’s policies, making it difficult to implement the European regulations. The development of the European identity will thereby eliminate the lack of coherence, internal and external balance and will allow an efficient execution of the European growth strategies. Identity management should therefore be an integral part of the strategic management process.